Biological Anthropology : An Introductory Reader - Michael Alan Park (Mc Graw Hill, 2008)
This supplementary reader offers both historical and contemporary articles that demonstrate the nature and significant contributions of biological anthropology. With nearly one-third of the selection focusing on living populations, the 42 readings cover the entire range of bioanthropological studies: evolution, nonhuman primates, human paleontology, and modern human groups.